Appreciating the Resilience and Stability Found in Heterogeneity: A South African Perspective on Urban Household Food Security - Nenguda, Rendani; Scholes, Mary Catherine (Frontiers in Sustainable Food Systems, 2022)
Urban food security has long been viewed as secondary to rural food security in South Africa, and with the migration of large numbers of people from rural to urban settings, it has become crucial to place more focus on urban food security. More so, in South African townships, where high unemployment rates amongst the youth exist. The interventions towards reducing food insecurity in urban settings are often taken from those previously designed for application in the rural context. In this study, the factors constraining and enhancing food security in Tembisa, South Africa were investigated, to gain an in-depth understanding of the drivers of urban food insecurity. To accomplish this, FANTA’s Household Food Insecurity Access Scale (HFIAS) was applied, which measures levels of food security and the Household Dietary Diversity Scale (HDDS), which measures the level of nutritional intake of households. Food prices of the formal and informal markets were also monitored over a period of 6 months. A significant decline in household food access over a four-year period (2013-2016) was observed in addition to relatively low-quality diets. The most commonly used coping methods during periods of low income included borrowing either money or food from friends and neighbours, this was sometimes done in conjunction with various other coping strategies. Much of the declining food access was attributed to the inflation of food prices, the lack of formal employment, and many household members to breadwinner ratios. High reliance solely on financial capital remains a limitation to the livelihood of urban households. Furthermore, government initiatives such as social grants and school feeding schemes have proven to be critical in reducing the vulnerability to food insecurity of most households.